The comparison of capacity and energy usage of two paddy planting method in IADA Barat Laut, Selangor / Mohammad Azrul Haziq Zulkifli - Zulkifli, Mohammad Azrul Haziq (Faculty of Plantation and Agrotechnology, 2017)
In this 21th century, paddy productions continue to improve its productivity by using technology. The technology use in paddy production is using mechanisation instead of using hand or animal assisted. In Malaysia, there are two types of paddy planting method that widely used by farmers; transplanter and direct-seeding. In IADA Barat Laut , Selangor from the survey that have been done, the farmers there unfortunately using these two methods without knowing the field capacity ,energy usage and the total cost involved. The parameters collected to fulfil the objectives are time taken (ha/hr), speed (km/hr), width of implement (m), number of run and fuel consumption. The result obtained shows that the transplanter gave higher field capacity (0.78 ha/hr) than direct-seeding (0.30 ha/hr). In field efficiency, transplanter gave higher percentage (%) where transplanter is (62%) and (59%) for direct-seeding. Next, the total energy used in transplanter also lowers than direct-seeding method which is (3094.54 MJ ha-1) and (3633.70 MJ ha-1). However, the costing for direct-seeding method is cheaper than using transplanter where (RM495) and (RM1470). As a conclusion, transplanter is more effective in time and can cover larger area even though the cost is higher than direct-seeding method.